1989
DOI: 10.1136/jcp.42.7.682
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological sampling of postmortem rooms.

Abstract: SUMMARY Thirty hospital and coroners' postmortem rooms in the West Midlands were visited over two years. The design, environmental facilities, and hygienic practices were investigated and air exchange rates were measured. Microbiological samples were taken from the environment and from gloves, hands, and protective clothing of staff. Glove punctures were also recorded and a plastic isolator evaluated. Bacterial counts in the air were low and related more to the number of people in the room than to the air exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
0
23
1
Order By: Relevance
“…Tangential support to this argument can be gleaned from the literature [11,29,34,43,70,75,84,87,89,92,100,104,125]. The hands of physicians are a known link in the transmission of nosocomial pathogens [70].…”
Section: Avoiding Dressing Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tangential support to this argument can be gleaned from the literature [11,29,34,43,70,75,84,87,89,92,100,104,125]. The hands of physicians are a known link in the transmission of nosocomial pathogens [70].…”
Section: Avoiding Dressing Changesmentioning
confidence: 99%
“…In the absence of gloves, there is a considerable increase in bacterial contamination of healthcare workers' hands after patient contact [75,87,100]. Numerous studies have investigated the rates of hand contamination after patient care, and hand contamination may occur even if gloves are worn [11,29,34,43,75,84,87,92,101,125].…”
Section: Avoiding Dressing Changesmentioning
confidence: 99%
“…In addition, it has also been stated that this parasite has a role in the pathogenesis of diseases by acting as a vector in the detection of some pathogenic organisms (eg, Hansen bacillus, Staphylococcus aureus, rickettsia, and certain viruses) and by providing a convenient environment for bacteria. [1][2][3][4][5][6][7][8]15,17 In this study, the relationship between certain factors reported to be effective in the occurrence of Demodex and cause the parasite to become pathogenic was investigated in physicians and autopsy technicians who work in the autopsy room.…”
mentioning
confidence: 99%
“…During procedures carried out on bodies in the autopsy room, slow viruses such as tuberculosis, hepatitis C virus (HCV), hepatitis B virus (HBV), human immunodeficiency virus (HIV), human T-cell lymphotropic virus (HTVL), CreutzfeltJakob, as well as Q-fever, Legionnaires disease, splenic fever, tetanus, typhoid, and paratyphoid factors, proteus, streptococcus, fungi, and ecto-and endoparasites carry a risk of contamination for the staff. [1][2][3][4][5][6][7] Sources mention risks of various infections for those working in the autopsy room. However, no reference has been made to the frequency rate of Demodex, which is an ectoparasite, in the health personnel working in the autopsy room.…”
mentioning
confidence: 99%
See 1 more Smart Citation